Toward a description of the conformations of denatured states of proteins. Comparison of a random coil model with NMR measurements - Fiebig, K; Schwalbe, H; Buck, M; Smith, L; Dobson, C (1996)
A strategy is proposed to describe the backbone conformations sampled in denatured states of proteins. Main chain dihedral angle distributions are extracted from the protein data base and used to predict NMR parameters such as coupling constants and NOE intensities. A simple model in which each residue samples its φ,ψ distribution noncooperatively has been found to reproduce many of the features of experimental NMR data for hen egg-white lysozyme denatured in 8 M urea at low pH. This model provides a framework which allows identification of residual structure inherent in experimental data of nonnative states of proteins. The effects of introducing local conformational cooperativity on NMR parameters are discussed and analyzed in light of the experimental data for lysozyme. © 1996 American Chemical Society.